In vitro mucus transportability, cytogenotoxicity, and hematological changes as non-destructive physiological biomarkers in fish chronically exposed to metals - Seriani, Robson [UNESP]; Abessa, Denis M. S. [UNESP]; Moreira, Lucas B. [UNESP]; Cabrera, Joana P. G.; Sanches, Juliana Q.; Silva, Carolina L. S.; Amorim, Francisca A.; Rivero, Dolores H. R. F.; Silva, Flavia L.; Fitorra, Lilian S.; Carvalho-Oliveira, Regiani; Macchione, Mariangela; et al. (Elsevier B.V., 2015)
The biomonitoring of fish using biomarkers represents a useful tool for the assessment of aquatic pollution. This study evaluated the sublethal toxic effects of aquatic pollution on fish collected from a site contaminated by metals. Water and fish (Oreochromis niloticus) samples were collected from a pond in the Parque Ecologico do Tiete (PET) that lies along the Tiete River (Sao Paulo, Brazil), and from a control site (an experimental fish farm). The metal content of the water was evaluated, and fish were used to examine the properties of gill mucus and blood. The PET fish were evaluated for alterations in the in vitro transportability of mucus and changes in blood properties (e.g., cell volume, hemoglobin concentration, red blood cells, and white blood cell count). The results of the water analyzes indicated metal levels above the legal standards for Fe (0.71 mg/L), Ni (0.06 mg/L), Mn (0.11 mg/L), and Pb (0.48 mg/L). Compared to the controls, the hematologic parameter analyzes of PET fish revealed significantly higher numbers of erythrocytes (RBC), leukocytes (WBC), lymphocytes, erythroblasts, and Mean Corpuscular Volume (MCV); however, the hemoglobin content and Mean Corpuscular Hemoglobin Concentration (MCHC) values were significantly lower. The frequencies of nuclear abnormalities and micronuclei were significantly higher and the mucociliary transport was significantly lower in PET fish than in the controls. These results suggest that fish from the contaminated site exhibit a series of physiological responses, which probably indicate health disturbances. Furthermore, the results suggest that blood and mucus are promising, non-destructive targets for use in the monitoring of pollution. (C) 2014 Elsevier Inc. All rights reserved.
Keywords: Biomarkers; Chronic contamination; Cyto-genotoxicity; Hematology; Metals; Mucus